A Study of Job Satisfaction among Teachers, Higher Secondary School of Nepal - Deepak P. Kayastha; Rabindra Kayastha (International Journal of Evaluation and Research in Education (IJERE), 2012)
This article investigates the job satisfaction among teachers with particular reference to corporate, Higher Secondary level School in Nepal. The job satisfactions that have been examined under this study include, work, pay, co-workers, supervision, promotion, job in general. The sample consists of a Government, Private and Public Higher Secondary level School teacher from Kathmandu and Latitpur District of Nepal. Data were collected using a questionnaire survey. The results show there is a significant relationship between job satisfaction facets.DOI: http://dx.doi.org/10.11591/ijere.v1i1.752